The male imago of Paramaka incognita Domínguez, Grillet, Nieto, Molineri and Guerrero, 2014 (Ephemeroptera: Leptophlebiidae) - Boldrini, R.; Barroso, P. C. S. (Zootaxa, 2015)
The genus Paramaka Savage & Domínguez, 1992 (Ephemeroptera: Leptophlebiidae) is restricted to South America, and it is comprised of four species. The male imago of P. incognita is described for the first time based on material from the state of Roraima in northern Brazil. The male adult differs from other described species of the genus by having the following combination of characteristics: Forewing with costal and subcostal areas basally washed with light yellowish brown; hind wing with base of wing washed with yellowish brown; abdominal terga II–V and VI–IX with lateral margins washed with reddish brown; abdominal sterna VI–VIII with lateral blackish stripes; styliger plate median portion with a pointed, posterior projection that is oriented in a posterior direction; and penes with ventral spines length subequal to length of penes, located on the distal third of the penes.